Wing-shaped plastic stents vs. self-expandable metal stents for palliative drainage of malignant distal biliary obstruction: a randomized multicenter study - Schmidt, Arthur; Riecken, Bettina; Rische, Susanne; Klinger, Christoph; Jakobs, Ralf; Bechtler, Matthias; Kähler, Georg; Dormann, Arno; Caca, Karel (Endoscopy, 2015)
Background and study aims: Previous studies have shown superior patency rates for self-expandable metal stents (SEMS) compared with plastic stents in patients with malignant biliary obstruction. The aim of this study was to compare stent patency, patient survival, and complication rates between a newly designed, wing-shaped, plastic stent and SEMSs in patients with unresectable, malignant, distal, biliary obstruction. Patients and methods: A randomized, multicenter trial was conducted at four tertiary care centers in Germany. A total of 37 patients underwent randomization between March 2010 and January 2013. Patients underwent endoscopic retrograde cholangiography with insertion of either a wing-shaped, plastic stent without lumen or an SEMS. Results: Stent failure occurred in 10/16 patients (62.5%) in the winged-stent group vs. 4/18 patients (22.2%) in the SEMS group (P=0.034). The median time to stent failure was 51 days (range 2–92 days) for the winged stent and 80 days (range 28–266 days) for the SEMS (P=0.002). Early stent failure (<8 weeks after placement) occurred in 8 patients (50%) vs. 2 patients (11.1%), respectively (P=0.022). After obtaining the results from this interim analysis, the study was discontinued because of safety concerns. Conclusions: The frequency of stent failure was significantly higher in the winged-stent group compared with the SEMS group. A high incidence of early stent failure within 8 weeks was observed in the winged-stent group. Thus, the winged, plastic stent without central lumen may not be appropriate for mid or long term drainage of malignant biliary obstruction.